Comportamiento clínico de un cemento biocompatible en la técnica endodóntica convencional con base en hidróxido de calcio - Valencia-R., Guillermo; Londoño-R., Maria Victoria; Arboleda-V., Lucia; Yepes-D., Fanny Lucia (Revista Facultad de Odontología Universidad de Antioquia, 2016)
It has been widely reported in dental literature the use and biological effect of calcium hydroxide in endodontics treatment and its mode of therapeutic action in endodontics (1). The aim of this study was to determine the evidence of an effect biocompatible when using calcium hydroxide in the endodontic treatment. Leonardo (2) suggests calcium hydroxide in order to get an apical seal before definitive root canal treatment in those cases named for him "Biopulpectomy" in some pulpal pathologies. This study was done in 105 mature teeth with root canal treatmentnecessity In each one of them it was used calcium hydroxide irrespective of the tooth diagnostic. The current work indicates a hig-hpercentag-e (93.4%) of success using a calcium hydroxide dressing in the root canal treatment. This result indicated that the calcium hydroxide improved the therapeutics conditions of the root canal sealer. In conclusion, the data suggest a relationship between the great percentage of root canal success, and the calcitlin hydroxide dreassing. Therefore it may offer a convenient method of routine endodontics treatment.